Within the lens of “keep”: the convergence of consumer context and brand development in Chinese fitness apps - Zhang, Xin; Kamarudin, Syafila; Tang, Qingqing; Cai, Yingying (Human Resources Management Academic Research Society (HRMARS), 2024)
The mobile internet's business strategies offer a new approach to traditional health communication's self-renewal. In China, where offline medical resources are scarce, leading sports applications (Apps) provide users with the ability to seek health solutions at any time, thereby helping to alleviate the strain on medical resources. However, there is still a relative scarcity of discussions on brand construction strategies for sports Apps. This study analyzes the Chinese sports mobile application 'Keep' as a case study. The research approach involves collecting data through external document analysis and observation, using a case analysis approach. The aim is to explore brand construction strategies for sports apps, with a focus on consumer scene construction. The research findings highlight 'Keep's' unique strengths, such as its wide target audience, exceptional experiential marketing, and significant content advantages. In the online consumer market, 'Keep' strategically focuses on cross-platform marketing, integrating high-quality courses, and synergizing with smart hardware. Offline, the emphasis shifts to promoting familiarity and creativity, with the introduction of innovative physical fitness projects. This understanding of 'Keep's' approach provides valuable insights for sports apps navigating the dynamic consumer landscape. In conclusion, our research not only illuminates the strategic intricacies of brand construction for sports apps but also provides actionable recommendations. As the industry evolves, establishing core strengths and cultivating meaningful connections with users are imperative for enhancing a sports app's communicative power. This study contributes to both academic discourse and practical applications in the sports app industry. It offers innovative perspectives for traditional health communication in the mobile internet era, benefiting practitioners, decision-makers, and researchers.